Oestradiol Contributes to Differential Antitumour Effects of Adjuvant Zoledronic Acid Observed Between Pre- and Post-Menopausal Women - Canuas-Landero, Victor G.; George, Christopher N.; Lefley, Diane V.; Corness, Hannah; Muthana, Munitta; Wilson, Caroline; Ottewell, Penelope D. (Frontiers in Endocrinology, 2021)
Clinical trials have demonstrated that adding zoledronic acid (Zol) to (neo)adjuvant standard of care has differential anti-tumour effects in pre- and post-menopausal women: Both benefit from reduced recurrence in bone, however, whilst post-menopausal women also incur survival benefit, none is seen in pre-menopausal women treated with adjuvant bisphosphonates. In the current study we have used mouse models to investigate the role of oestradiol in modulating potential anti-tumour effects of Zol. Pre-, peri- and post-menopausal concentrations of oestradiol were modelled in BALB/c wild-type, BALB/c nude and C57BL/6 mice by ovariectomy followed by supplementation with oestradiol. Mice also received 20mg/kg/day goserelin to prevent ovariectomy induced increases in FSH. Metastasis was modelled following injection of MDA-MB-231, 4T1 or E0771 cells after ovariectomy and saline or 100ug/kg Zol administered weekly. Supplementing ovariectomised mice with 12.5mg/ml, 1.38mg/ml and 0ng/ml oestradiol, in the presence of goserelin, resulted in serum concentrations of 153.16 +/- 18.10, 48.64 +/- 18.44 and 1.00 +/- 0.27pg/ml oestradiol, which are equivalent to concentrations found in pre-, peri- and post-menopausal humans. Osteoclast activity was increased 1.5-1.8 fold with peri-and post- menopausal compared with pre-menopausal oestradiol resulting in a 1.34-1.69 fold reduction in trabecular bone. Zol increased trabecular bone in all groups but did not restore bone to volumes observed under pre-menopausal conditions. In tumour bearing mice, Zol reduced bone metastases in BALB/c (wild-type and nude) with greatest effects seen under pre- and post-menopausal concentrations of oestradiol. Zol did not affect soft tissue metastases in immune competent BALB/c mice but increased metastases 3.95 fold in C57BL/6 mice under pre-menopausal concentrations of oestradiol. In contrast, Zol significantly reduced soft tissue metastases 2.07 and 4.69 fold in immune competent BALB/c and C57BL/6 mice, under post-menopausal oestradiol mirroring the results of the clinical trials of (neo)adjuvant bisphosphonates. No effects on soft tissue metastases were observed in immune compromised mice and differences in anti-tumour response did not correlate with MAF CAPG or GIPC1 expression. In conclusion oestradiol contributes to altered anti-tumour effects of Zol observed between pre- and post- menopausal women. However, other immunological/microenvironmental factors are also likely to contribute to this phenomenon.